In Situ Growth Measurements of Sodium Sulfate during Cooling Crystallization. Issue 8 (9th July 2014) - Egan, Tim; Rodriguez‐Pascual, Marcos; Lewis, Alison; Qu, Haiyan; Rantanen, Jukka; Ulrich, Joachim
Abstract Combined rainbow Schlieren deflectometry (RSD) and liquid crystal thermography (LCT) served as in situ non‐intrusive techniques to determine local concentration and temperature fields based on refractive index gradients in solution during crystallization of sodium sulfate from aqueous solution. The combination of RSD with LCT allowed the decoupling of concentration and temperature effects. Convective mass transport happened during periods of fast, dendritic growth, but even higher levels occurred during the densification of the dendritic crystals, indicating significant mass deposition in this phase. The convection developed mainly as a result of concentration gradients as opposed to temperature gradients. A supersaturation field map was generated and growth kinetics of the sodium sulfate salt was determined. The kinetics followed a power law relationship, with constants in line with those in the literature.